Kinerja Dinas Pekerjaan Umum Dan Tata Ruang Kota Salatiga Dalam Pengembangan Tata Ruang Wilayah Tahun 2016 (Studi Kasus Taman Tingkir Kota Salatiga) - Nahar, Akhmad Lutfi; Munandar, Moh. Aris; Susanti, Martien Herna (Unnes Political Science Journal, 2017)
Salatiga city is currently facing the influence over the function expansion of land where affected by the development of spatial locality. Public works-human settlements and Spatial planning Salatiga city as one of the Government agencies involved in standardization of spatial one public place to ensure the balance of the ecosystem of the city. Tingkir Park as one of place who became a city park and the activities of the citizens of most crowded at this time. Where is the year 2011-2016 public place in Salatiga city is just 15.9% meet the standard of 30%. Required performance improvements and spatial planning which can accommodate all kinds of activities to support the scope better. The issues examined in this study are (1) How the implementation of a performance carried out by the Department of public works and town of Salatiga in Spatial Development Tingkir Park in Salatiga city? (2) what factors affect the performance conducted Public works-human settlements and Spatial planning in Salatiga city spatial development in the region of the year 2016 (Case study on Tingkir Park, Salatiga)? This research in a research combination (mixed methods) with a model sequential exploratory. Research locations in the public works and of the city spatial salatiga and Tingkir Park. A kind of method research with qualitative and quantitative approaches with the methods discriptive. The focus of this study is to understand the implementation of the and the factors influences the performance of Public works-human settlements and Spatial planning in Salatiga pertaining with Tingkir park. The population and sample obtained using formulas Frank Lynch. Data collection in this research using interviews, the questionnaire, observation, documentation. The result of this research is the implementation of the performance of Public works-human settlements and Spatial planning in Salatiga in case study Tingkir park less fulfill standard green open space in Salatiga city with the central government 15.9 % of standard 30 %. But based on the research done through prespektif the community 60,3 % totally agree with an average 80,0 % so people really agree and satisfied with the Tingkir park in salatiga city. After the Tingkir park, management less well until facilities damaged. As: game children and tiles. Factors that influences performance management department of Public works-human settlements and Spatial planning in Salatiga city seen from the individual, a personal capacity, and factors motivation. Where third this factor in public works agency and spatial planning prefer the ability and education. Employees to will be exposed through expression attitudes and the act of employees can perform the task and functions well. Advice for Salatiga city government should always involve the community in each phase because communities understand more what they want related policies implemented. And always optimize the implementation of performance management until progress of development of facilities and infrastructure that unkempt and efficiently beeing good. Salatiga Goverment must always support and provide development of facilities and infrastructure like city parks that not only stop on building the park stage but until the maintenance and supervision to ensure the maintenance functions with good infrastructure.